IMPLIKASI PROGRAM KEMPUS MENGAJAR TERHADAP MAHASISWA PAI UNIVERSITAS AHMAD DAHLAN YOGYAKARTA - firdha ayu Hafidah (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2022)
Abstract Merdeka Learning Campus Merdeka is a policy aimed at universities to oversee the transformation of higher education, this policy is stated in Permendikbud Number 3 of 2020 concerning National Higher Education Standards. With this policy, students are encouraged to collaborate with the business world, industry and the general public. Among the MBKM programs, namely campus teaching programs, campus teaching programs, namely teaching is carried out by students in educational units such as elementary, middle, and high schools. The purpose of this study is to find out how the implications obtained by students in participating in the campus teaching program.Schools where teaching practice can be located in urban or remote areas. The purpose of this teaching department is for students to devote themselves to this country and students are able to help the problems faced by schools that are still lagging behind. It also aims to produce a good graduate and keep up with the times. In this study the authors use qualitative research methods by using the method (field research) field studies conducted directly by the author. The author gets the primary data from students who pass the campus teaching program and is supported by secondary data from journals and books. As for the results of the study found that. The teaching campus is one of the MBKM programs pioneered by the Ministry of Education and Culture. With this program, it is hoped that students can hone their dreams and they can go directly to the community and be able to help solve problems in schools that are lagging behind. Students will also be expected to become graduates who are competent and able to keep up with the times. The implementation of this teaching and learning program for pai Uad students certainly has their own experience when they go directly to the community and they gain knowledge how to be able to provide good learning, they are able to compete in facing challenges along with the times. They are able to help solve problems in schools that are lagging behind, starting from administration, learning order and others. Keywords: Impication, teaching campus, Students, Pai Uad